Chapter 10 Pluralism and Allocation of Limited Resources Vaccines and Ventilators - Wilkinson, Dominic (Oxford University Press, 2023)
In the response to this pandemic, two vital, but controversial ethical questions are we should allocate ventilators to patients with severe respiratory failure, and how we should distribute vaccines to people at risk of contracting coronavirus. There There are opposing ethical views about how to prioritise, and countries have taken different different differentdifferentapproaches. There There is a strong ethical argument that policies should take a pluralistic approach to allocation that reflectsreflects reflectsreflectsreflectsmultiple ethical values - both because of the diversity of viewpoints within communities and the recognition that there are competing relevant ethical values. In this chapter, I look at the epistemic and normative problems raised by pluralistic allocation in this pandemic and suggest implications for future pandemics. I summarise some of the relevant evidence about the public's views and values relating to prioritisation. I also explore some practical approaches to prioritisation of scarce resources in the face of contrasting and competing ethical values